2019
DOI: 10.1103/physrevb.100.115145
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Faraday and Kerr rotation spectroscopy of Bi1xSbx films in high magnetic fields up to 30 tesla

Abstract: We report results of terahertz Faraday and Kerr rotation spectroscopy measurements on thin films of Bi1−xSbx, an alloy system that exhibits a semimetal-to-topological-insulator transition as the Sb composition x increases. By using a single-shot time-domain terahertz spectroscopy setup combined with a table-top pulsed mini-coil magnet, we conducted measurements in magnetic fields up to 30 T, observing distinctly different behaviors between semimetallic (x < 0.07) and topological insulator (x > 0.07) samples. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…It should be noted that both Faraday and Kerr rotation signals can be extracted in a transmission configuration. [34][35][36][37] The THz pulse that directly transmits through the sample contains only the Faraday rotation signal. Nevertheless, the back reflection pulse experiences both Faraday and Kerr rotation due to additional reflection events at the interfaces.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that both Faraday and Kerr rotation signals can be extracted in a transmission configuration. [34][35][36][37] The THz pulse that directly transmits through the sample contains only the Faraday rotation signal. Nevertheless, the back reflection pulse experiences both Faraday and Kerr rotation due to additional reflection events at the interfaces.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, polarization-dependent THz spectroscopy allows one to determine both the diagonal and off-diagonal elements of the conductivity tensor through Faraday and Kerr rotations. 34,37,[56][57][58][59][60][61]…”
Section: Plasmonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobility and concentration of electrons and holes in the trigonal plane (the film plane) were calculated using Equations (7)- (9). Calculation takes into account that solid solutions of bismuth-antimony are intrinsic semimetals which means that they have equal concentrations of electrons and holes.…”
Section: Resistivity Magnetoresistivity and Hall Coefficientmentioning
confidence: 99%
“…Many studies are dedicated to investigation of dependency of Bi 1−x Sb x sheet DC conductivity on antimony content, film thickness, and temperature [1][2][3][4][5]. In two recent works it was shown that thin bismuth-antimony films have tunable optical response in the THz frequency range [8,9]. In the work of Katayama et al, the optical response of charge carriers was investigated in thin films of Bi and Bi 1−x Sb x (x from 0 to 16 %) in a frequency range up to 50 THz, but the measurements were performed only for film thickness of 40 nm [8].…”
Section: Introductionmentioning
confidence: 99%